2009
DOI: 10.4049/jimmunol.182.1.538
|View full text |Cite
|
Sign up to set email alerts
|

The Bacterial Fermentation Product Butyrate Influences Epithelial Signaling via Reactive Oxygen Species-Mediated Changes in Cullin-1 Neddylation

Abstract: The human enteric flora plays a significant role in intestinal health and disease. Populations of enteric bacteria can inhibit the NF-κB pathway by blockade of IκB-α ubiquitination, a process catalyzed by the E3-SCFβ-TrCP ubiquitin ligase. The activity of this ubiquitin ligase is regulated via covalent modification of the Cullin-1 subunit by the ubiquitin-like protein NEDD8. We previously reported that interaction of viable commensal bacteria with mammalian intestinal epithelial cells resulted in a rapid and r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
78
1
2

Year Published

2009
2009
2022
2022

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 108 publications
(84 citation statements)
references
References 77 publications
(96 reference statements)
3
78
1
2
Order By: Relevance
“…It has been demonstrated that 70% of the oxygen consumption in colonic cells comes from the oxidation of SFCAs, particularly butyrate 29 . In segments without a fecal stream, the absence of dietetic fibers and changes to the normal bacterial flora decrease the production, absorption and use of SFCAs by the epithelial cells, leading to the overproduction of ROS 30 . The importance of adequate oxidation of SCFAs in the prevention of DC is known through clinical and experimental studies showing that rectal instillation with SCFAs in diverted colon segments reduces the inflammatory process 14,16 .…”
Section: Discussionmentioning
confidence: 99%
“…It has been demonstrated that 70% of the oxygen consumption in colonic cells comes from the oxidation of SFCAs, particularly butyrate 29 . In segments without a fecal stream, the absence of dietetic fibers and changes to the normal bacterial flora decrease the production, absorption and use of SFCAs by the epithelial cells, leading to the overproduction of ROS 30 . The importance of adequate oxidation of SCFAs in the prevention of DC is known through clinical and experimental studies showing that rectal instillation with SCFAs in diverted colon segments reduces the inflammatory process 14,16 .…”
Section: Discussionmentioning
confidence: 99%
“…For example, it has been shown recently that Mycobacterium ulcerans induces ROS formation in epidermal keratinocytes via TLRdependent pathways (Lee et al, 2009). By contrast, fermentation products derived from commensal bacteria of the gut flora also induce ROS production in intestinal epithelial cells resulting in neddylation of cullin 1 and suppression of NFκB signalling (Kumar et al, 2007;Kumar et al, 2009). Thus generation of ROS is a common event, initiated by both harmless bacteria and pathogens.…”
Section: Discussionmentioning
confidence: 99%
“…This bacterium-induced ROS generation modulates numerous cellular functions, including transient oxidative inactivation of enzymes required for modulating cullin-dependent signaling (10,11), inducing extracellular signal-regulated kinase (ERK)-specific signaling (12), and potentiating epithelial restitution via redox inactivation of focal adhesion kinase phosphatases (13). We also showed that specific taxa composing the microbiota, especially those within the genus Lactobacillus, can directly stimulate intestinal stem cell growth and accelerate epithelial growth during homeostasis (8) or wound healing by redox-dependent mechanisms involving NADPH oxidase 1 (14).…”
mentioning
confidence: 99%